Modern Features of Internet Communications in the Supply Chain Management Sector in Various Countries of the World - Tkhorikov, Boris A.; Kornev, Vladimir V.; Gerasimenko, Olga A.; Lesovik, Ruslan V.; Lesovaya, Svetlana L.; Ageykina, Mariya E. (ExcelingTech, 2020)
Abstract- The article is devoted to the problems of information and communication problems and the potential of activity of supply chain management in them. The relationship between the level of increasing the democratization of socio-economic processes and the dialogue between members of the government and society has been revealed. A promising platform for these processes is web space. In different countries, a special relationship to the content and content of social networks of government representatives. According to the authors, supply chain management should be the most active, since it is they who are interested in the electorate to participate in electoral events